PENGARUH PENGENDALIAN INTERN DAN PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA MANAJERIAL - Triadi, A.A Lina; Suputra, I.D.G Dharma (E-Jurnal Akuntansi, 2016)
These research having an intention to analyze the authority of the internal control and the application of Good Corporate Governance principles on managerial performance. Managerial performance quantity is the one of important factor for company. Manager must be able to decipher the vision strategy in order to become concrete steps and it carried out. The data handpicked by using purposive sampling. The correspondents in this research are the staff of PT BRI (persero) Tbk. Branch Denpasar at or to the managerial level and chief executive (SPV). The collecting data used the questionnaire. After collecting the data later in processed and analyzed by SPSS version 17. Statistic method can applied to examine the hypothesis is multiple regressions. The result of this research as follows: I) the internal power has significant influence toward the managerial performance positively. 2) The application of Good Corporate Governance principles has significant influence toward the managerial performance positively.
Keywords: Managerial Performance, Internal Control, Good Corporate Governance Principles